2008
DOI: 10.1258/ijsa.2008.008099
|View full text |Cite
|
Sign up to set email alerts
|

Commercial sex and HIV transmission in mature epidemics: a study of five African countries

Abstract: The study compares the association between using the services of commercial sex workers and male HIV seroprevalence in five African countries: Ghana, Kenya, Lesotho, Malawi and Rwanda. The HIV seroprevalence among men who 'ever paid for sex' was compared with controls who 'never paid for sex'. Results were based on 12,929 eligible men, aged 15-59 years, interviewed in Demographic and Health Surveys. The odds ratio of HIV seroprevalence associated with ever paying for sex was 1.89 (95% confidence interval = 1.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…Indeed, prevalence was even higher among FSW who reported not knowing their HIV status at the time of the survey (26%). Overall prevalence among FSW in our study is 3 times the 2005 DHS+ estimate of 8.0% HIV prevalence among women in Kigali [5], although it falls within the general range reported by other studies among sex workers in the sub-Saharan region [11], [24][30]. It is likely, however, that HIV prevalence among FSW was underestimated in our study because we excluded known HIV-positives.…”
Section: Discussionsupporting
confidence: 62%
“…Indeed, prevalence was even higher among FSW who reported not knowing their HIV status at the time of the survey (26%). Overall prevalence among FSW in our study is 3 times the 2005 DHS+ estimate of 8.0% HIV prevalence among women in Kigali [5], although it falls within the general range reported by other studies among sex workers in the sub-Saharan region [11], [24][30]. It is likely, however, that HIV prevalence among FSW was underestimated in our study because we excluded known HIV-positives.…”
Section: Discussionsupporting
confidence: 62%
“…However, contrary to Talbott, we did not find an association between FSW population size estimates and HIV prevalence in the general population (in our study, HIV prevalence among pregnant women was used as proxy for general population prevalence). This study was however highly criticised for the vagueness of the country data on numbers of FSWs,16 even by the authors who published the data on FSW population size estimates,17 as well as for the positions taken by the non-governmental association chaired by the author on sex work and HIV,18 that could have influenced choices in his analyses, and the strength of his conclusions, given the limitations of ecological analyses 19…”
Section: Discussionmentioning
confidence: 99%
“…The 4-city study conducted in the late 1990's concluded that commercial sex could not explain differential prevalence within the sites [30]. We showed from five case studies in the early 2000s that the role of female sex workers seems limited, and accounts for only 1.3 to 9.4% of infections in the general population, although Zambia was not included in this sample [56]. To a certain extent, results of our simulation H0 reflect this fact.…”
Section: Discussionmentioning
confidence: 70%